ANALISIS FENOL DALAM URIN PEKERJA SALAH SATU STASIUN PENGISIAN BAHAN BAKAR UMUM DI KOTA DENPASAR - Abdul Rahim; Ni Made Suaniti; Wiwik Susanah Rita (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
Phenol is a compound produced by the metabolism of benzene contained in the fuel. The purpose of this study was to determine the content of phenol in the urine of workers at a Public Gas Station in Denpasar. The method used in this analysis was gas chromatography – FID (GC-FID). Urine was taken 3 times with an interval of 7 days from 3 workers. Control was taken from a non-gas station worker. Standard solutions used were mixtures of benzene and phenol with concentration of 1.25, 2.50, 5, and 10 ppm. Phenol calibration curve equation was y = 2.94x ??+ 0.23 with a correlation coefficient (r) = 0.9997. The concentration of phenol of samples varied ranging from 0.51 ppm to 1.38 ppm, while the phenol content in gasoline alone was 0.66 ppm. Phenol levels in the urines were still under normal value which is 25 ppm, while the level of benzene exposure was still under the standard concentration of 10 ppm.